2D ANIMATE CREATION ‘PRODIGAL SON’ GESTALT MOVS - Darmawan, Andreas James; Arimbawa, I Made Gede; Muka, I Ketut; Suardina, I Nyoman (International Journal of Social Science, 2025)
The creation of the 'Prodigal Son' animation stems from the author's realization of the need for fresh and engaging church teaching media for youth aged 12-17. Current media often lack appeal, as they focus only on storylines without offering deeper engagement. This gap highlights the urgency to develop new media that effectively delivers story essence using the Gestalt MoVS(Movement on Voice and Spirit) visual style. The study addresses how to create animation that fills this gap, applies Gestalt MoVS concepts, and visualizes the 'Prodigal Son' story through this approach. Utilizing a descriptive qualitative method and practice-based research, the process includes literature studies on Gestalt MoVS theory, theological philosophy, hermeneutics, semiotics, VCD (Visual Communication Design) principles, and expert interviews with theologians, animators, media experts, and adolescent psychologists. Media trials with targeted audiences also contribute to the visual analysis. The result is an aesthetically pleasing animation that conveys the story's three main essences—repentance, forgiveness, and gratitude—in a paradoxical configuration, addressing both repentant audiences and those who judge others. The animation offers an innovative solution to engage teens and simplify Bible story delivery, emphasizing an interdisciplinary approach to inspire spiritual understanding and real-life application.